Scale Model Test on Inexperienced Acoustic Vibrations Occurred in the Operation of a Heat Exchanger - KAWAOKA, Takayoshi; SHIRAKI, Kazuhiro; SATO, Yuichi; TSUBOI, Mamoru; KATAYAMA, Keiichi (Transactions of the Japan Society of Mechanical Engineers Series C, 1999)
In the operation of a tubular heat exchanger, or a gas heater, occurred acoustic vibrations, which could not be suppressed at all by installing baffle plates along the gas flow into the tube bundle of the gas heater. Baffle plates along the gas flow are always very effective in suppression of acoustic vibrations so far. To clarify the cause of the vibration phenomenon, we built a three-dimensional airflow scale model using the similarity method. Accordingly, violent vibrations took place, which have the same characteristic as the gas heater. We conclude that the model test method we conducted is useful to check the normal operation of a gas heater.